Evaluation Analysis of Community-Based Quran Memorization Program Odoj: Integration of CIPP Model with Community Evaluation in Quran Memorization Education in Indonesia - M. Ahim Sulthan Nuruddaroini; Kusaeri Kusaeri (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2023)
This research aims to analyze the evaluation of the odoj community-based tahfizh quran program. This research uses Systematic Literature Review, which is indexed in Scopus using the Zotero, Publish or Perish application, publications from international journals such as Eric, Taylor, and Francis, and Google Scholar using the PRISMA technique. After going through the identification, screening, eligibility, and inclusion phases 482 articles, making 46 articles selected as research data. This research shows that 1) The odoj phenomenon is an interesting movement in the Indonesian Islamic world, with its large number of communities spread both at home and abroad. They also come from various circles, including students, students, the general public, and artists. Odoj has recruited more than 140,000 followers ranging from children as young to adults as old. 2) There are several evaluation models that can be applied in the field of education of Tahfizh Quraan, namely the CIPP model, STAKE model, Self-Assessment, Formative and Summative Evaluation,Group Decision Support System (GDSS), Gamification Learning for Al-Quran Memorizing (GLAM-Q. 3) If you see the limitations of the CIPP model, it is necessary to innovate a new evaluation model, namely: how to integrate the CIPP model evaluation with the odoj community in the Quran tahfizh program. Especially in the aspects of context evaluation, input evaluation, process evaluation which are carried out together (community). This study provides an important contribution in developing a more effective and contextual evaluation model for community-based Quran memorization programs, which can improve the quality of memorization education in Indonesia.